(3aVGFd ecI GdecQeIs - (3GdHUQj, CHh SYjO, GdMSf Hf jSGQ, (B110 (3g`s ((3EHQGgje Hf Ndjd GdcGTGfjs)
(3ChdgG (B:s
(3HSe Gddg CNHQfG GdTjN Gdabjg Cf CHG GdMSf Hf Ydj Hf Ydj GdMGVQI Hf Ydj GdHZOGOj HGdbSWGW bGd CNHQfG CHh Ydj MSjf Hf YHO GdQMef GdTGaYj HecI bGd CNHQfG CHh GdMSf Ydj Hf YHO Gddg GdgeOGfj s
(3BNQgG (B:s
(3hef Udi Nda GdebGe QcYJjf ZaQ dg eG JbOe ef PfhHg hCYWi ef GdMSfGJ HYOO cd ef Udi Ndag CVYGaG eVGYaI hBefg Gddg JYGdi jhe GdbjeI ef GdaRY GdCcHQ hCeQ Gddg YR hLd LHQGFjd hejcGFjd Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\226s
(3gOjI GdYGQajf (B1\265s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs